LncRNA plasmacytoma variant translocation 1 is an oncogene in bladder urothelial carcinoma - Liu, Zhongyuan (Oncotarget, 2017)
Bladder cancer (BC) is the most lethal malignant cancer of the genitourinary system, and bladder urothelial carcinoma (BUC) is the most common type of BC. The long non-coding RNA (lncRNA) plasmacytoma variant translocation 1 (PVT1) is overexpressed in several malignant tumors, including BC. Using a lncRNA array and quantitative real-time PCR, we detected greater expression of PVT1 in BUC tissues and cell lines resistant to doxorubicin (DOX) and cisplatin (DDP) than in DOX- and DDP-sensitive cells. PVT1 knockdown reduced proliferation and invasion by a DOX- and DDP-resistant T24/DR BUC cells, arrested cells in G1 phase, and increased apoptosis. PVT1 knockdown also sensitized T24/DR cells to DOX and DDP, and suppressed expression of multidrug resistance 1 (MDR1) and multidrug resistance associated protein 1 (MRP1). Wnt/β-catenin pathway activation in T24/DR cells reversed the effects of PVT1 knockdown on metastasis-associated behavior and chemoresistance. In sum, lncRNA PVT1 is overexpressed in multidrug resistant BUC tissues and cell lines, and PVT1 knockdown reduces BUC cell proliferation, invasiveness, and chemoresistance by modulating Wnt/β-catenin signaling. These results provide new insight into BUC chemoresistance mechanisms and suggest potential therapeutic targets for anti-BUC therapeutics.